Confessional Fracture in Ukraine as a Projection of the Global Geopolitical Process - A. V. Ishin (Проблемы постсоветского пространства, 2023)
The article analyzes the confessional rift in Ukraine as a projection of the global geopolitical process. The nature of the repressive policy of official Kyiv in relation to canonical Orthodoxy is considered in detail. The unprecedented pressure that the state institutions of Ukraine and the neo-nazi formations supported by them are currently exerting on Ukraine’s largest traditional confession, the Ukrainian Orthodox Church, is a consequence of the gradual introduction of long-term geopolitical stratagems of the opponents of the Russian World. The author believes that the open support from the collective West of the arbitrariness of the Kyiv regime in the confessional space of Ukraine should be considered in the light of the fundamental geopolitical tasks of the Euro-Atlantic structures. The author comes to the conclusion that their goal is the final disorientation of the Ukrainian society, ensuring the unhindered colonization of a number of Ukrainian territories, turning them into a stable zone of Western interests, openly hostile to Russia. It is natural that representatives of other traditional confessions are also victims of the ethno-confessional policy of official Kyiv. Today, in the world community, all people of common sense should unite in defense of the fundamental principle of freedom of conscience, which fully meets the criteria of basic human rights, enshrined in the fundamental acts of international law.